Assessing cognitive changes in the elderly: reliable change indices for the mini-mental state examination - Stein, Janine; Weyerer, Siegfried (Acta psychiatrica Scandinavica, 2012)
Objective: The diagnosis of dementia includes evidence of decline in cognitive functioning over time measured by objective cognitive tasks. Normative data for changes adjusted for the impact of socio-demographic factors on cognitive test performance are lacking to interpret changes in Mini-Mental State Examination (MMSE) test scores. Method: As part of the German Study on Ageing, Cognition and Dementia in Primary Care Patients (AgeCoDe Study), a sample of 1090 cognitively healthy individuals, aged 75 years and older, was assessed at 1.5-year intervals over a period of 4.5 years using the MMSE. Age- and education-specific Reliable Change Indices (RCIs) were computed. Results: Age and education were significantly associated with MMSE test performance, and gender indicated no impact. Across different age and education subgroups, changes from at least 2 up to 3 points indicated significant (i.e., reliable) changes in MMSE test scores at the 90% confidence level. Furthermore, the calculation of RCIs for individual patients is demonstrated. Conclusion: This study provides age- and education-specific MMSE norms based upon RCI methods to interpret cognitive changes in older age groups. The computation of RCI scores improves the interpretation of changes in MMSE test scores by controlling for measurement error, practice effects, or regression to the mean.
Gesehen am 11.09.2018
*Further members of the AgeCoDe Study Group: Heinz-Harald Abholz, Cadja Bachmann, Wolfgang Blank, Sandra Eifflaender-Gorfer, Annette Ernst, Kathrin Heser, Frank Jessen, Hanna Kaduszkiewicz, Teresa Kaufeler, Carolin Lange, Tobias Luck, Manfred Mayer, Julia Olbrich, Anna Schumacher, Susanne Steinmann, Franziska Tebarth, Klaus Weckbecker, Dagmar Weeg, Thomas Zimmermann